Islamic Economics: Principles and Applications in Contemporary Finance - Melisa Tiran (GoAcademica Research & Publishing, 2023)
This scientific journal article aims to explore the fundamental principles and applications of Islamic economics in the context of contemporary financial systems. Islamic economics is an emerging field that adheres to the principles of Sharia, the Islamic law, and emphasizes ethical and moral considerations in economic activities. The paper begins with an overview of the underlying principles of Islamic economics and then examines its application in various financial sectors. It also analyzes the potential benefits and challenges of incorporating Islamic economic principles into mainstream finance. The article concludes by discussing the future prospects and implications of Islamic economics in the global financial landscape.